Reconfiguring resources for strategic posture: Changes of entrepreneurial orientation through acquisition - Jan Conrads; Mareike Heinzen; Matthias Baum (Journal of Open Innovation: Technology, Market and Complexity, 2023)
In order to pursuit opportunities for growth and competitive advantage, firms reconfigure resources for becoming more entrepreneurial-oriented, i.e. more innovative, risk-taking and proactive in decision-making. As an important part of corporate strategy, firms incorporate external resources, e.g. through business acquisitions. Therefore, we study the emergence of entrepreneurial orientation (EO) within an organization by investigating if major business acquisitions alter an acquiring firm’s EO. We measure the acquiring firm’s EO by computer-aided text analysis (CATA) before, during and after an acquisition as historic events by screening letter to shareholders of US-Fortune 1000 companies. Our results from a sample of 202 firms show that companies closing major acquisitions have a significantly higher level of innovativeness while being more risk-averse in different phases of the acquisition process. Additionally, the relatedness (i.e. operating in the same industrial sector) between the acquiring firm and the target firm positively moderates the relationship between closing a major acquisition deal and innovativeness growth. For practitioners, our findings indicate that firms can spur their innovativeness by acquiring companies that operate in the same industrial sector, thus reconfiguring resources in a more productive way and in the same line of business.